Exploring the impact of grazing on fecal and soil microbiome dynamics in small ruminants in organic crop-livestock integration systems. - Sejin Cheong; Kimberly Aguirre-Siliezar; Sequoia R Williams; Amélie C M Gaudin; Paulo Pagliari; Michele T Jay-Russell; Roselle Busch; Elizabeth A Maga; Alda F A Pires (PLoS ONE)
In integrated crop-livestock systems, livestock graze on cover crops and deposit raw manure onto fields to improve soil health and fertility. However, enteric pathogens shed by grazing animals may be associated with foodborne pathogen contamination of produce influenced by fecal-soil microbial interactions. We analyzed 300 fecal samples (148 from sheep and 152 from goats) and 415 soil samples (272 from California and 143 from Minnesota) to investigate the effects of grazing and the presence of non-O157 Shiga toxin-producing Escherichia coli (STEC) or generic E. coli (gEc) in fecal and soil microbiomes. We collected samples from field trials of three treatments (fallow, a cover crop without grazing (non-graze CC), and a cover crop with grazing (graze CC)) grazed by sheep or goats between 2020 and 2022. No significant differences in non-O157 STEC prevalence were found between pre- and post-grazing fecal samples in either sheep or goats. However, gEc was more prevalent in graze CC soils compared to fallow or non-graze CC soils. Alpha diversity was influenced by the species of grazing animals and the region, as sheep fecal samples and soil from the California trials had greater alpha diversity than goat fecal samples and soil from the Minnesota trials. Beta diversity in sheep fecal samples differed by the presence or absence of non-O157 STEC, while in goat fecal samples, it differed between pre- and post-grazing events. Actinobacteria was negatively associated with non-O157 STEC presence in sheep fecal samples and decreased in post-grazing goat fecal samples. Grazing did not significantly affect soil microbial diversity or composition, and no interaction was observed between post-grazing fecal samples and the graze CC soil. The results suggest that soil contamination by foodborne pathogens and microbiome dynamics in ICLS are influenced by grazing animal species and regional factors, with interactions between fecal and soil microbial communities having minimal impact.